Cultural difference in neural mechanisms of self-recognition. - Sui, J; Liu, C; Han, S (2009)
Self-construals are different between Western and East Asian cultures in that the Western self emphasizes self-focused attention more, whereas the East Asian self stresses the fundamental social connections between people more. To investigate whether such cultural difference in self-related processing extends to face recognition, we recorded event-related potentials from British and Chinese subjects while they judged head orientations of their own face or a familiar face in visual displays. For the British, the own-face induced faster responses and a larger negative activity at 280-340 ms over the frontal-central area (N2) relative to the familiar face. In contrast, the Chinese showed weakened self-advantage in behavioral responses and reduced anterior N2 amplitude to the own-face compared with the familiar face. Our findings suggest that enhanced social salience of one's own face results in different neurocognitive processes of self-recognition in Western and Chinese cultures.